Improving Learners' Literacy to Face the Educational Challenges of the Digital Age at SMA 2 Batanghari - Hidayat, M.; Amnie, Erlida; Veronika Sirait , Jeliana; Lestari, Neneng; Jufrida, Jufrida (Pendidikan Sejarah FKIP Universitas JAMBI, 2024)
Challenges in the digital era require students to have strong digital literacy, especially in utilising technology wisely. This service activity aims to improve the digital literacy skills of students at SMA 2 Batanghari. This includes improving the ability to think critically, creatively and collaborate in the digital space. The method used includes preparation, implementation and evaluation stages. The discussion of digital literacy material aims to build a safe environment and educate students about positive digital media practices. Digital literacy is expected to help students become responsible and wise users of technology. Evaluation assessment was conducted using questionnaires before and after the activity (pretest and posttest). The results of the questionnaire showed that there was an increase in students' digital literacy skills with a medium level N-Gain category. Based on the data obtained, the activities carried out were effective in improving students' understanding and digital literacy skills. This service activity is expected to be a provision in facing technological challenges in the digital era. A deep understanding of the impact of digital media and how to use it is expected to lead learners to be ready to face challenges in the digital era.